Initial losses from rainfall in the Lower Himalayas of Uttar Pradesh-A study in Hydrology of the Region - Naithani, RC (Journal of Soil and Water Conservation, 2022)
The initial losses of rainfall technically known as interception and evaporation from depression storage need to be known correctly before runoff and infiltration rates can be determined fairly accurately for hydrological studies of a basin. The classical paper on the subject is that by Horton (1919) in which he expressed the total storm interception in the equation